CRISPR interference-based specific and efficient gene inactivation in the brain - Zheng, Yi; Shen, Wei; Zhang, Jian; Yang, Bo; Liu, Yao-Nan; Qi, Huihui; Yu, Xia; Lu, Si-Yao; Chen, Yun; Xu, Yu-Zhou; Li, Yun; Gage, Fred H.; et al. (Nature neuroscience, 2018)
CRISPR–Cas9 has been demonstrated to delete genes in postmitotic neurons. Compared to the establishment of proliferative cell lines or animal strains, it is more challenging to acquire a highly homogeneous consequence of gene editing in a stable neural network. Here we show that dCas9-based CRISPR interference (CRISPRi) can efficiently silence genes in neurons. Using a pseudotarget fishing strategy, we demonstrate that CRISPRi shows superior targeting specificity without detectable off-target activity. Furthermore, CRISPRi can achieve multiplex inactivation of genes fundamental for neurotransmitter release with high efficiency. By developing conditional CRISPRi tools targeting synaptotagmin I ( Syt1 ), we modified the excitatory to inhibitory balance in the dentate gyrus of the mouse hippocampus and found that the dentate gyrus has distinct regulatory roles in learning and affective processes in mice. We therefore recommend CRISPRi as a useful tool for more rapid investigation of gene function in the mammalian brain. CRISPR interference-based gene silencing was adopted to achieve highly efficient multiple and conditional gene knockdown in the mouse brain with negligible off-target effects, providing a rapid gene interrogation tool in the mammalian brain.